Rolled copper foil for flexible printed circuit board and preparation method thereof
By adding specific alloy components to the calendered copper foil for flexible printed circuit boards and performing optimization process processing, the problem of inconcentrating cubic texture orientation of copper foil after recrystallization and annealing is solved, and its flexural performance and conductivity are significantly improved.
Patent Information
- Application Number
- CN202411797060.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
AI Technical Summary
The calendered copper foil for flexible printed circuit boards is not oriented in a cubic texture after recrystallization annealing, resulting in poor flexural performance.
By configuring alloy components, forming process and controlling heat treatment process, texture regulation is realized and the generation of cubic texture after recrystallization and annealing is promoted. The specific method includes adding elements such as Ag, La, Ce, Nd to the copper alloy, and regulating grain orientation and texture characteristics through multiple passes of cold rolling and annealing.
The flexural performance and conductivity of copper alloy foil are significantly improved. The flexural performance of annealed copper foil can reach up to 36,000 times and the conductivity can reach up to 105% IACS.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a rolled copper foil for a flexible printed circuit board and a preparation method thereof. Background Art
[0002] With the advent of the 5G era, people's demand for various portable electronic devices is increasing, such as folding mobile phones, smart watches, laptops, etc., which are constantly developing in the direction of lightweight, high speed and multifunctionality. The performance of conventional electrolytic copper foil and rolled copper foil can no longer meet market demand. Flexible rolled copper foil, as an indispensable core basic material in the electronic information industry, is an important component of conductor connection and signal transmission in various electronic components. Due to its excellent conductivity, thermal conductivity, flexibility, low surface roughness, and alloyability, it is widely used in the manufacture of flexible circuit boards (FPCs), lithium-ion battery negative electrode carriers, electromagnetic shielding bodies and other products. The use of FPC can greatly reduce the size of electronic products and meet the needs of my country's electronic products to gradually shift towards high density, miniaturization, and high reliability.
[0003] During the production process of flexible printed circuit boards, the rolled copper foil and the base layer need to be bonded at a certain temperature. During this process, the copper foil softens. In order to ensure that the copper foil has high flexural properties, it is often required to have a lower recrystallization temperature, a larger recrystallized grain size, and a higher recrystallized grain orientation consistency. However, such technology is still lacking in China. Although there are production lines and products for flexible rolled copper foil, their performance is still far behind that of related foreign products.
[0004] With the rapid development of high-end electronic equipment, new energy vehicles and high-end manufacturing industries in my country, higher requirements are placed on the performance of rolled copper foil. Copper foil is prone to work hardening during the rolling process. In order to improve the plastic deformation ability of copper foil, it is often necessary to perform intermediate annealing between the rough rolling and finishing rolling processes. The temperature or holding time of the intermediate annealing will directly affect the final forming quality of the rolled copper foil. Recrystallization annealing can optimize the grain orientation of the rolled copper foil and further improve the electrical properties of the rolled copper foil. Therefore, in order for the rolled copper foil for flexible printed circuit boards to meet the performance requirements, the copper foil must have a high degree of grain orientation consistency after recrystallization and a cubic texture cube{001} <100> It can improve the bending resistance and flexibility of copper foil, reduce the skin effect, and thus improve the transmission efficiency of signals, meeting the needs of rolled copper foil in practical applications. At present, the biggest problem of rolled copper foil for flexible printed circuit boards is that the cubic orientation of recrystallized grains after annealing is not concentrated, and the flexural performance is poor. Therefore, a new type of highly flexible copper alloy foil is needed to meet production needs. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a rolled copper foil for a flexible printed circuit board and a preparation method thereof, by configuring the synergistic effect of alloy composition, forming process and controlling the heat treatment process to achieve texture regulation, promote the generation of cubic texture after recrystallization annealing, and thereby achieve the purpose of improving the flexibility and conductivity of the copper alloy foil.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides a rolled copper foil for a flexible printed circuit board, which is composed of the following components in mass percentage: Ag: 0.002-0.005wt%, La: 0.01-0.1%, Ce: 0.01-0.05%, Nd: 0.05-0.25%, O: 0.01-0.1%, and the balance is Cu and inevitable impurities.
[0008] Preferably, it is composed of the following components in mass percentage: Ag: 0.003wt%, La: 0.08%, Ce: 0.05%, Nd: 0.2%, O: 0.1%, and the balance is Cu and inevitable impurities.
[0009] The present invention provides a method for preparing a rolled copper foil for a flexible printed circuit board, comprising the following steps:
[0010] Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 0.5-20Pa, then control the power of the smelting furnace to 4-4.4KW, increase it to maintain a constant 6.6KW after preheating for 5 minutes, raise the temperature to 1100-1150°C, then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 7-15 minutes, then quickly add rare earth elements after the raw materials are fully melted, stir them slightly after melting, adjust the power to 3KW, continue to keep warm for 3-5 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain an alloy ingot;
[0011] Step 2: Place the alloy ingot into a heat treatment furnace for homogenization treatment at a homogenization temperature of 950-980°C, control the holding time to be 3-6 hours, and cool to room temperature with the furnace. The thickness of the obtained alloy ingot is 0.4-0.6mm;
[0012] Step 3: heat the homogenized alloy ingot to 600-620°C, keep it warm for 30 minutes, then hot roll it, the total deformation of hot rolling is 40-70%, and then water cool it to room temperature, the thickness of the alloy strip is 0.15-0.3mm;
[0013] Step 4: After removing the surface oxide scale of the hot-rolled alloy strip, cold rolling is performed at room temperature, and the total rolling deformation is 88-94%; the rolling process is 7-8 passes, and the deformation of each pass is 20-50%; the first pass processing rate is 35-40%, the second pass processing rate is 35-50%, the third pass processing rate is 30-40%, and the subsequent single pass processing rate is 20-25%, and the thickness of the obtained alloy foil is 17-20 μm;
[0014] Step 5: placing the cold-rolled alloy foil in a heat treatment furnace for annealing at a temperature of 180-200° C. for 1 hour, followed by air cooling to room temperature to obtain the rolled copper foil for the flexible printed circuit board.
[0015] Preferably, in step 3, the total hot rolling deformation is 40%.
[0016] Preferably, in step 4, the total rolling deformation is 94%, of which the first pass processing rate is 40%, the second pass processing rate is 50%, the third pass processing rate is 35%, and the subsequent single pass processing rate is 20%, and the thickness of the obtained alloy ingot is 19μm.
[0017] Preferably, in step 2, the surface of the alloy ingot is milled and then placed in a heat treatment furnace for homogenization treatment.
[0018] Preferably, in step 2, the thickness of the alloy ingot obtained is 0.5 mm.
[0019] The purity of the high-purity Cu and Cu-Ag master alloy is 99.99%.
[0020] The beneficial effects of the present invention are:
[0021] The present invention overcomes the problems of low cube orientation content and low flexibility of traditional copper foil after recrystallization annealing by designing alloy composition, optimizing rolling process and other methods, and provides a solution for the preparation of high-pressure rolled copper foil materials for flexible printed circuit boards.
[0022] The present invention obtains a rolled copper foil with highly concentrated cube texture orientation, low recrystallization temperature and excellent flexural performance by optimizing alloy composition, rolling method and other processes. The copper alloy material after composition optimization is subjected to multiple cold rolling processes with large deformation, so that the grains are broken, the grains are refined, the cold rolling texture content is increased, and the recrystallization temperature of the material is reduced. Moreover, by controlling the deformation amount of a single pass, the morphology and distribution characteristics of the deformation band and texture of the final cold rolled state structure can be regulated.
[0023] On the one hand, the addition of trace silver and rare earth elements can significantly change the cold-rolled deformation structure of copper alloy foil. The solid solution strengthening effect of alloying elements will increase the strength of the material and inhibit the occurrence of dynamic recrystallization, thereby causing more fine grains and increasing the dislocation density in the deformed structure; on the other hand, the presence of alloying elements also promotes the movement and cross-slip of dislocations, making the deformation texture distribution more uniform. By controlling the deformation amount of different passes during the cold rolling process, the texture composition, distribution and proportion of the final cold-rolled sample can be regulated. In the early stage of the recrystallization annealing process, the S{123} <634> Texture, Copper{112} <111> A large number of recrystallized nuclei will appear at the junction of the texture and deformation band. Among them, the grain boundary energy of the recrystallized grains with cube texture orientation is low, which is conducive to the merging and growth of grains. It has a significant advantage in grain growth during the subsequent annealing process. After one hour of annealing, the cube texture accounts for as much as 90%, and the flexural performance of the annealed copper foil is as high as 36,000 times.
[0024] The present invention regulates the cold rolling texture characteristics by adding trace Ag, rare earth elements, appropriate oxygen content and adjusting the cold rolling process on the basis of traditional pure copper foil. The addition of trace silver can improve the toughness of copper, thereby reducing the formation of cracks, promoting the formation and evolution of deformation bands, and making the deformation bands more complete and continuous. During the cold rolling process, the addition of silver will affect the movement and interaction of dislocations, resulting in a more uniform distribution of deformation bands. The addition of rare earth elements has a significant effect on the generation and slip behavior of dislocations. Trace amounts of La, Ce, and Nd can reduce the generation rate of dislocations, inhibit the interaction of dislocations, and lead to a reduction in dislocation density. At the same time, the addition of trace rare earth elements will affect the texture evolution of copper. The presence of rare earth elements can promote the growth of specific grain orientations, such as S{123} <634> Texture, Copper{112} <111> Texture, thus changing the texture characteristics after cold rolling. Appropriate oxygen content helps to improve plasticity, keep the dislocation density in a suitable range, promote the cross-slip of dislocations, make the deformation band more uniform, and reduce local strain concentration. Changes in oxygen content will also affect the texture of copper foil after cold rolling. Appropriate amount of oxygen can promote the formation of certain textures, such as <111> Orientation is beneficial to the plastic deformation of the material, while too high oxygen content will lead to the deterioration of the texture.
[0025] A small deformation amount in a single pass during the cold rolling process will result in a small number of deformation bands and uneven deformation bands; a small deformation amount will also lead to insufficient texture development, resulting in unsatisfactory texture after cold rolling. An increase in the deformation amount in a single pass will significantly increase the dislocation density, forming a more complex dislocation network, aggravating the local stress concentration phenomenon, and may lead to increased brittleness and reduced ductility. The present invention optimizes the composition and process, so that the deformation bands after cold rolling are uniform and complete, and the boundaries between different deformation bands are clear. Among them, {123} <634> and {112} <111> The texture is evenly distributed along the RD direction, and its content is higher than other types of textures, such as: {011} <211> 、{011} <100> 、{124} <211> During the recrystallization annealing process, the nucleation sites of recrystallized grains with cube texture orientation increase significantly, so the content of cube texture is greatly improved, thereby improving the flexibility of copper foil.
[0026] The present invention solves the problems of low flexibility and high recrystallization temperature of rolled copper foil for flexible printed circuit boards. The comprehensive performance is improved through new alloy design and process optimization, making it suitable for the manufacture of high-demand flexible printed circuit boards. The copper alloy foil designed by the present invention has excellent flexural performance and electrical conductivity. The flexural performance of the annealed copper foil can reach up to 36,000 times, and the electrical conductivity can reach up to 105% IACS. DETAILED DESCRIPTION
[0027] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0028] Embodiment 1:
[0029] This embodiment discloses a rolled copper foil material for a flexible printed circuit board, the composition content of which is: Ag: 0.002wt%, La: 0.05%, Ce: 0.01%, Nd: 0.2%, O: 0.06%, and the balance is Cu and unavoidable impurities.
[0030] A method for preparing a rolled copper foil material for a flexible printed circuit board in this embodiment comprises the following steps:
[0031] Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 10Pa, then control the power of the smelting furnace to 4KW, preheat for 5 minutes, then increase it to maintain a constant 6.6KW, heat it to 1100℃, and then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep it warm for 7 minutes, then quickly add rare earth elements after the raw materials are fully melted, stir it slightly after melting, reduce the power to 3KW, continue to keep warm for 3 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain an alloy ingot;
[0032] Step 2: Mill the surface of the ingot, and then put it into the heat treatment furnace for homogenization treatment. The homogenization temperature is 950°C, the holding time is controlled to be 4h, and it is cooled to room temperature with the furnace. The sample thickness is 0.5mm;
[0033] Step 3: The homogenized ingot is heated to 600°C, kept at this temperature for 30 minutes, and then hot rolled. The total deformation of the hot rolling is 60%, and then water cooled to room temperature. The sample thickness is 0.2 mm.
[0034] Step 4: After removing the surface oxide scale of the hot-rolled alloy material, rolling is performed at room temperature, and the total deformation of rolling is 90%. The number of processing passes is 7, and the deformation of each pass is 25-35%. Among them, the processing rate of the first pass is 35%, the processing rate of the second pass is 35%, the processing rate of the third pass is 30%, and the subsequent single pass processing rate is 25%. The final sample thickness is 20μm;
[0035] Step 5: placing the cold-rolled alloy material into a heat treatment furnace for annealing at a temperature of 180° C. for 1 hour, followed by air cooling to room temperature to obtain the rolled copper foil for the flexible printed circuit board.
[0036] The copper-silver alloy foil obtained in this example has a cube texture content of 66%, a flexural performance of 33,200 times, and an electrical conductivity of 98.5% IACS.
[0037] Embodiment 2:
[0038] This embodiment discloses a rolled copper foil material for a flexible printed circuit board, the composition content of which is: Ag: 0.002wt%, La: 0.01%, Ce: 0.05%, Nd: 0.25%, O: 0.01%, and the balance is Cu and unavoidable impurities.
[0039] A method for preparing a rolled copper foil material for a flexible printed circuit board in this embodiment comprises the following steps:
[0040] Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 0.5Pa, then control the power of the smelting furnace to 4.4KW, preheat for 5 minutes, then increase and maintain it at 6.6KW, heat it to 1150℃, then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 15 minutes, then quickly add rare earth elements after the raw materials are fully melted, stir them slightly after melting, reduce the power to 3KW, continue to keep warm for 5 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain a copper-silver alloy ingot;
[0041] Step 2: Mill the surface of the ingot, and then put it into the heat treatment furnace for homogenization treatment. The homogenization temperature is 980°C, the control time is 6 hours, and the ingot is cooled to room temperature with the furnace. The sample thickness is 0.5mm;
[0042] Step 3: The homogenized ingot is heated to 620°C, kept at this temperature for 30 minutes, and then hot rolled. The total deformation of the hot rolling is 60%, and then water cooled to room temperature. The sample thickness is 0.2 mm.
[0043] Step 4: After removing the surface oxide scale of the hot-rolled alloy material, rolling is performed at room temperature, and the total deformation of rolling is 90.5%. The number of processing passes is 7, and the deformation of each pass is 20-40%. Among them, the processing rate of the first pass is 35%, the processing rate of the second pass is 40%, the processing rate of the third pass is 40%, and the subsequent single pass processing rate is 20%. The final sample thickness is 19μm;
[0044] Step 5: placing the cold-rolled alloy material into a heat treatment furnace for annealing at a temperature of 180° C. for 1 hour, followed by air cooling to room temperature to obtain the rolled copper foil for the flexible printed circuit board.
[0045] The copper-silver alloy foil obtained in this example has a cube texture content of 48%, a flexural performance of 32,100 times, and an electrical conductivity of 92.2% IACS.
[0046] Embodiment 3:
[0047] This embodiment discloses a rolled copper foil material for a flexible printed circuit board, the composition content of which is: Ag: 0.005wt%, La: 0.05%, Ce: 0.05%, Nd: 0.2%, O: 0.07%, and the balance is Cu and unavoidable impurities.
[0048] A method for preparing a rolled copper foil material for a flexible printed circuit board in this embodiment comprises the following steps:
[0049] Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 15Pa, then control the power of the smelting furnace to 4.2KW, preheat for 5 minutes, then increase and maintain it at 6.6KW, raise the temperature to 1120°C, then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 10 minutes, then quickly add rare earth elements after the raw materials are fully melted, stir them slightly after melting, reduce the power to 3KW, continue to keep warm for 5 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain a copper-silver alloy ingot;
[0050] Step 2: Mill the surface of the ingot, and then put it into the heat treatment furnace for homogenization treatment. The homogenization temperature is 950°C, the control time is 3 hours, and the ingot is cooled to room temperature with the furnace. The sample thickness is 0.5mm;
[0051] Step 3: The homogenized ingot is heated to 600°C, kept at this temperature for 30 minutes, and then hot rolled. The total deformation of the hot rolling is 40%, and then water cooled to room temperature. The sample thickness is 0.3 mm.
[0052] Step 4: After removing the surface oxide scale of the hot-rolled alloy material, rolling is performed at room temperature, and the total deformation of rolling is 93.7%. The number of processing passes is 8, and the deformation of each pass is 20-50%. Among them, the processing rate of the first pass is 40%, the processing rate of the second pass is 50%, the processing rate of the third pass is 35%, and the subsequent single pass processing rate is 20%. The final sample thickness is 19μm;
[0053] Step 5: placing the cold-rolled alloy material into a heat treatment furnace for annealing at a temperature of 180° C. for 1 hour, followed by air cooling to room temperature to obtain the rolled copper foil for the flexible printed circuit board.
[0054] The copper-silver alloy foil obtained in this example has a cube texture content of 79%, a flexural performance of 34,000 times, and an electrical conductivity of 101.6% IACS.
[0055] Embodiment 4:
[0056] This embodiment discloses a rolled copper foil material for a flexible printed circuit board, the composition content of which is: Ag: 0.003wt%, La: 0.08%, Ce: 0.05%, Nd: 0.2%, O: 0.1%, and the balance is Cu and unavoidable impurities.
[0057] A method for preparing a rolled copper foil material for a flexible printed circuit board in this embodiment comprises the following steps:
[0058] Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 20Pa, then control the power of the smelting furnace to 4.3KW, preheat for 5 minutes, then increase and maintain it at 6.6KW, raise the temperature to 1130°C, and then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 15 minutes, then quickly add rare earth elements after the raw materials are fully melted, stir them slightly after melting, reduce the power to 3KW, continue to keep warm for 5 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain a copper-silver alloy ingot;
[0059] Step 2: Mill the surface of the ingot, and then put it into the heat treatment furnace for homogenization treatment. The homogenization temperature is 980℃, the control time is 5h, and the ingot is cooled to room temperature with the furnace. The sample thickness is 0.5mm;
[0060] Step 3: The homogenized ingot is heated to 620°C, kept at this temperature for 30 minutes, and then hot rolled. The total deformation of the hot rolling is 70%, and then water cooled to room temperature. The sample thickness is 0.15 mm.
[0061] Step 4: After removing the surface oxide scale of the hot-rolled alloy material, rolling is performed at room temperature, and the total deformation of rolling is 88.7%. The number of processing passes is 7, and the deformation of each pass is 20-40%. Among them, the processing rate of the first pass is 35%, the processing rate of the second pass is 40%, the processing rate of the third pass is 30%, and the subsequent single pass processing rate is 20%. The sample thickness is 17μm;
[0062] Step 5: placing the cold-rolled alloy material into a heat treatment furnace for annealing at a temperature of 180° C. for 1 hour, followed by air cooling to room temperature to obtain the rolled copper foil for the flexible printed circuit board.
[0063] The copper-silver alloy foil obtained in this example has a cube texture content of 84%, a flexural performance of 34,700 times, and an electrical conductivity of 103.1% IACS.
[0064] Embodiment 5:
[0065] This embodiment discloses a rolled copper foil material for a flexible printed circuit board, the composition content of which is: Ag: 0.003wt%, La: 0.08%, Ce: 0.05%, Nd: 0.20%, O: 0.1%, and the balance is Cu and unavoidable impurities.
[0066] A method for preparing a rolled copper foil material for a flexible printed circuit board in this embodiment comprises the following steps:
[0067] Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 20Pa, and then control the power of the smelting furnace to 4.4KW, preheat for 5 minutes, then increase and maintain it at 6.6KW, raise the temperature to 1150°C, and then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 15 minutes, and then quickly add rare earth elements after the raw materials are fully melted, stir them slightly after melting, reduce the power to 3KW, continue to keep warm for 5 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain a copper-silver alloy ingot;
[0068] Step 2: Mill the surface of the ingot, and then put it into the heat treatment furnace for homogenization treatment. The homogenization temperature is 980℃, the control time is 5h, and the ingot is cooled to room temperature with the furnace. The sample thickness is 0.5mm;
[0069] Step 3: The homogenized ingot is heated to 620°C, kept at this temperature for 30 minutes, and then hot rolled. The total deformation of the hot rolling is 40%, and then water cooled to room temperature. The sample thickness is 0.3 mm.
[0070] Step 4: After removing the surface oxide scale of the hot-rolled alloy material, rolling is performed at room temperature, and the total deformation of rolling is 93.7%. The number of processing passes is 8, and the deformation of each pass is 20-50%. Among them, the processing rate of the first pass is 40%, the processing rate of the second pass is 50%, the processing rate of the third pass is 35%, and the subsequent single pass processing rate is 20%. The final sample thickness is 19μm;
[0071] Step 5: placing the cold-rolled alloy material into a heat treatment furnace for annealing at a temperature of 180° C. for a holding time of 1 h, followed by air cooling to room temperature to obtain the copper alloy material.
[0072] The copper-silver alloy foil obtained in this example has a cube texture content of 91%, a flexural performance of 35,100 times, and an electrical conductivity of 105.3% IACS.
[0073] Embodiment 6:
[0074] This embodiment discloses a rolled copper foil material for a flexible printed circuit board, the composition content of which is: Ag: 0.005wt%, La: 0.1%, Ce: 0.05%, Nd: 0.15%, O: 0.1%, and the balance is Cu and unavoidable impurities.
[0075] A method for preparing a rolled copper foil material for a flexible printed circuit board in this embodiment comprises the following steps:
[0076] Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 20Pa, then control the power of the smelting furnace to 4.3KW, preheat for 5 minutes, then increase and maintain it at 6.6KW, heat it to 1140°C, then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 10 minutes, then quickly add rare earth elements after the raw materials are fully melted, stir them slightly after melting, reduce the power to 3KW, continue to keep warm for 5 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain a copper-silver alloy ingot;
[0077] Step 2: Mill the surface of the ingot, and then put it into the heat treatment furnace for homogenization treatment. The homogenization temperature is 950°C, the control time is 6 hours, and the ingot is cooled to room temperature with the furnace. The sample thickness is 0.5mm;
[0078] Step 3: The homogenized ingot is heated to 620°C, kept at this temperature for 30 minutes, and then hot rolled. The total deformation of the hot rolling is 40%, and then water cooled to room temperature. The sample thickness is 0.3 mm.
[0079] Step 4: After removing the surface oxide scale of the hot-rolled alloy material, rolling is performed at room temperature, and the total deformation of rolling is 93.7%. The number of processing passes is 8, and the deformation of each pass is 20-50%. Among them: the processing rate of the first pass is 40%, the processing rate of the second pass is 50%, the processing rate of the third pass is 35%, and the subsequent single pass processing rate is 20%. The final sample thickness is 19μm;
[0080] Step 5: placing the cold-rolled alloy material into a heat treatment furnace for annealing at a temperature of 180° C. for 1 hour, followed by air cooling to room temperature to obtain the rolled copper foil for the flexible printed circuit board.
[0081] The copper-silver alloy foil obtained in this example has a cube texture content of 73%, a flexural performance of 33,700 times, and an electrical conductivity of 98.7% IACS.
[0082] Comparative Example:
[0083] The rolled copper foil material for the flexible printed circuit board of this embodiment has the following components: Cu: 99.99 wt %, and the remainder is inevitable impurities.
[0084] A method for preparing a rolled copper foil material for a flexible printed circuit board in this embodiment comprises the following steps:
[0085] Step 1: Add the raw material Cu into the crucible, evacuate to 10Pa, then control the power of the smelting furnace to 4KW, preheat for 5 minutes, then increase and maintain it at 6.6KW, raise the temperature to 1100℃, then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 5 minutes, wait for the raw material to be fully melted, then reduce the power to 3KW, continue to keep warm for 3 minutes, and after all the raw materials are melted evenly, quickly cast them into the mold to obtain a pure copper ingot;
[0086] Step 2: Mill the surface of the ingot, and then put it into the heat treatment furnace for homogenization treatment. The homogenization temperature is 950°C, the holding time is controlled to be 4h, and it is cooled to room temperature with the furnace. The sample thickness is 0.5mm;
[0087] Step 3: The homogenized ingot is heated to 600°C, kept at this temperature for 30 minutes, and then hot rolled. The total deformation of the hot rolling is 60%, and then water cooled to room temperature. The sample thickness is 0.2 mm.
[0088] Step 4: After removing the surface oxide scale of the hot-rolled material, cold rolling is performed at room temperature. The total rolling deformation is 89.5%, the number of processing passes is 11, the deformation of a single pass is 20%, and the final sample thickness is 21 μm;
[0089] Step 5: placing the cold-rolled alloy material into a heat treatment furnace for annealing at a temperature of 180° C. for a holding time of 1 h, followed by air cooling to room temperature to obtain the copper foil material.
[0090] The raw material of the comparative example is Cu, and the main difference between the processing method and the above embodiment is that the comparative example adopts a common cold rolling process, and the deformation amount of each pass of the process is consistent. The copper foil prepared by the composition and method of the comparative example has a cube texture content of 36%, a flexural performance of 29,000 times, and an electrical conductivity of 80.8% IACS.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A rolled copper foil for a flexible printed circuit board, characterized in that: The following components are present in percentage by weight Composition: Ag: 0.002-0.005wt%, La: 0.01-0.1%, Ce: 0.01-0.05%, Nd: 0.05-0.25%, O: 0.01-0.1%, and the balance is Cu and inevitable impurities.
2. The rolled copper foil for a flexible printed circuit board according to claim 1, characterized in that: The following components are present in percentage by weight Composition: Ag: 0.003wt%, La: 0.08%, Ce: 0.05%, Nd: 0.2%, O: 0.1%, and the balance is Cu and inevitable impurities.
3. The method for preparing a rolled copper foil for a flexible printed circuit board according to claim 1, characterized in that: The steps include: Step 1: After grinding and removing the oxide scale from each raw material, prepare it according to the mass percentage of each component, add the prepared high-purity Cu and Cu-Ag master alloy into the crucible in turn, evacuate to 0.5-20Pa, then control the power of the smelting furnace to 4-4.4KW, increase it to maintain a constant 6.6KW after preheating for 5 minutes, raise the temperature to 1100-1150°C, then introduce argon into the furnace, smelt under the protection of pure argon atmosphere, keep warm for 7-15 minutes, then quickly add rare earth elements after the raw materials are fully melted, stir them slightly after melting, adjust the power to 3KW, continue to keep warm for 3-5 minutes, and after the raw materials are evenly melted, quickly cast them into a mold to obtain an alloy ingot; Step 2: Place the alloy ingot into a heat treatment furnace for homogenization treatment at a homogenization temperature of 950-980°C, control the holding time to be 3-6 hours, and cool to room temperature with the furnace. The thickness of the obtained alloy ingot is 0.4-0.6mm; Step 3: heat the homogenized alloy ingot to 600-620°C, keep it warm for 30 minutes, then hot roll it, the total deformation of hot rolling is 40-70%, and then water cool it to room temperature, the thickness of the alloy strip is 0.15-0.3mm; Step 4: After removing the surface oxide scale of the hot-rolled alloy strip, cold rolling is performed at room temperature, and the total rolling deformation is 88-94%; the rolling process is 7-8 passes, and the deformation of each pass is 20-50%; wherein the first pass processing rate is 35-40%, the second pass processing rate is 35-50%, the third pass processing rate is 30-40%, and the subsequent single pass processing rate is 20-25%, and the thickness of the obtained alloy foil is 17-20 μm; Step 5: placing the cold-rolled alloy foil in a heat treatment furnace for annealing at a temperature of 180-200° C. for 1 hour, followed by air cooling to room temperature to obtain the rolled copper foil for the flexible printed circuit board.
4. The method for preparing a rolled copper foil for a flexible printed circuit board according to claim 3, characterized in that: In step 3, the total amount of hot rolling deformation is 40%.
5. The method for preparing a rolled copper foil for a flexible printed circuit board according to claim 3, characterized in that: In step 4, the total rolling deformation is 94%, of which the first pass processing rate is 40%, the second pass processing rate is 50%, the third pass processing rate is 35%, and the subsequent single pass processing rate is 20%. The thickness of the obtained alloy foil is 19 μm.
6. The method for preparing a rolled copper foil for a flexible printed circuit board according to claim 3, characterized in that: In the step 2, the surface of the alloy ingot is milled and then placed in a heat treatment furnace for homogenization treatment.
7. The method for preparing a rolled copper foil for a flexible printed circuit board according to claim 3, characterized in that: In step 2, the thickness of the alloy ingot obtained is 0.5 mm.